Effectively relevant varieties of the physical qualities of football (soccer) players at the stage of specialized basic training - Линець [Mykhaylo Lynets], Михайло Михайлович; Трохимчук [Nazar Trokhymchuk], Назар Андрійович; Войтович [Ivan Voytovych], Іван Петрович (Slobozhanskyi Herald of Science and Sport, 2013)
Purpose of the research consists in determining the availability of efficient and meaningful indicators of physical preparedness in 15–16 years old football players. We applied pedagogical observation combined with instrumental methods of research. Twenty four reliable (p≤0,05) correlations between quantitative efficiency indicators of technical and tactical actions (TTA) in conditions of competitive activities and the level of physical fitness has been found, 13 direct and 11 inverse indicators among them. The largest number of meaningful direct interrelations of CA indicators was registered between the development of strength and speed-strength skills and the latent time of simple audio-motor and complex visual-motor reactions in 15–16 years old football players.